Combining Fischer-Tropsch Synthesis (FTS) and Hydrocarbon Reactions in one Reactor - Mena Subiranas, Alba (KIT Scientific Publishing, 2009)
The present study addresses the combination of low-temperature Fischer-Tropsch synthesis (FTS) and hydrocarbon modification reactions (hydroprocessing) in one reactor. The objective of the present investigation was to study the influence of CO during hydroprocessing reactions of hydrocarbon model compounds on two different bifunctional catalysts. In addition, the influence of the catalyst-bed configuration for the combination FTS and hydrocarbon reactions was investigated.